MyKICT: design and development of mobile application for course pre-registration - Ali, Osman; Kader Mohideen, Muhammad Khalid; Salleh, Norsaremah (Institute of Electrical and Electronics Engineers Inc., 2016)
Pre-registration of courses for upcoming semesters has always been a challenging task for many students. This includes the difficulty to identify suitable courses to be enrolled that follows the correct study plans provided by the department for the pre-registration. Students also tend to overlook important events or dates which are associated with their enrolled courses such as quizzes and project report deadline. In our feasibility study, we have conducted a survey among International Islamic University Malaysia (IIUM) students to help identify the possibility to overcome the said problem by developing an interactive mobile application. Hence, in this paper we present the development of mobile application that could help suggests courses to be enrolled for upcoming semesters and notifies students on the important events of their currently enrolled courses on real time basis. This system is called MyKICT Student App.